Propensity to Work Among Chronically Unemployed Adult Drug Users - Sigurdsson, Sigurdur Oli (2010)
Analyses were conducted to compare rates of employment before, during, and after employment at the therapeutic workplace, which is a novel employment-based treatment for drug misuse. Participants in two clinical trials attended the therapeutic workplace at higher rates than they worked before intake and six months after discharge. These data suggest that unemployed chronic drug misusers will attend work at higher rates at the therapeutic workplace than in the community when paid modest wages, and that the failure of chronic drug misusers to obtain employment in the community may not result from lack of interest in work.